Giant cell arteritis: Its ophthalmic manifestations - Hayreh, Sohan Singh (Indian J Ophthalmol, 2021)
Giant cell arteritis (GCA) is the most important medical emergency in ophthalmology, because its most dreaded complication is visual loss, which is preventable if these patients are diagnosed early and treated immediately and aggressively. This is a brief review of GCA, its ophthalmic manifestations, and how to diagnose and manage them.